2020
DOI: 10.3892/etm.2020.8496
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of p16INK4a, Ki‑67 and ProExC immuno‑qualitative features in LSIL progression into HSIL

Abstract: The current nested case-control study was conducted to explore the prognostic value of cyclin-dependent kinase inhibitor 2A (p16 INK4a), marker of proliferation Ki-67 (Ki-67) and immunohistochemical cocktail containing antibodies directed against topoisomerase IIα (TOP2A) and minichromosome maintenance 2 (MCM2) proteins (ProExC) immuno-qualitative features to predict low-grade squamous intraepithelial lesion (LSIL) progression. A total of 92 LSIL patients were followed-up for 2 years, where those with high-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
(40 reference statements)
2
15
0
Order By: Relevance
“…Several histological studies have reported the application of most common cellular biomarkers, including Ki-67, cyclin-dependent kinase inhibitor (p16), and ProEx C [topoisomerase II-alpha (TOP2A) and minichromosomal maintenance-2 (MCM2)] in the early diagnosis of cervical cancer [ 14 17 ]. Recently, Ki-67 has been demonstrated to be an important cell proliferation biomarker for malignant lesions among women in Tanzania [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several histological studies have reported the application of most common cellular biomarkers, including Ki-67, cyclin-dependent kinase inhibitor (p16), and ProEx C [topoisomerase II-alpha (TOP2A) and minichromosomal maintenance-2 (MCM2)] in the early diagnosis of cervical cancer [ 14 17 ]. Recently, Ki-67 has been demonstrated to be an important cell proliferation biomarker for malignant lesions among women in Tanzania [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several cancer biomarkers, especially when applied individually, may not detect cervical cancer as it develops, making them unsuitable for early diagnosis of cervical cancer [ 16 , 20 , 21 ]. However, a combination of biomarkers may improve the sensitivity and specificity of cancer detection in discriminating altered cells from normal cells across age groups [ 14 , 15 , 21 23 ]. During the pathogenesis of cervical cancer, the expression of E7 viral oncoprotein inactivates retinoblastoma proteins (pRb), which consequently increases the E2F activation factors in the cell, which leads to increased p16 in the S-phase of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Quin Shi et al, 2019) which is similar to the present study. Ding et al, (2020) reported the importance of both P16 INK4a and Ki-67 immunostaining in the LSIL category to predict the outcome in future as their study provides new insight into identifying LSIL patients at a higher risk of malignant progression, potentially facilitating more cost-effective and efficient interventions (Ding et al, 2020). The limitation of our study is the small sample size.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, Ding et al recently demonstrated that women with an initial diagnosis of LSIL by ProEx™ C immunostaining have a higher risk of developing HSIL in the next two years. They showed that this test might achieve a sensitivity of 75.0%, specificity of 64.5%, PPV of 30.8%, and NPV of 92.40% in LSIL lesions that may progress to HSIL [142]. Therefore, these overall results suggest that TOP2A/MCM2 biomarkers have excellent performance for both low and highgrade lesions.…”
Section: Top2a and Mcm2mentioning
confidence: 90%